Marker-trait Association for Resistance to Sugarcane Mosaic Virus (SCMV) in a Sugarcane (Saccharum spp.) Panel - Burbano, Roberto C. V. [UNESP]; da Silva, Marcel F. [UNESP]; Coutinho, Alisson E. [UNESP]; Gonçalves, Marcos C.; dos Anjos, Ivan A.; Anjos, Luciana O. S.; Perecin, Dilermando [UNESP]; Pinto, Luciana R. (Springer Nature, 2022)
Sugarcane mosaic disease (SMD) caused by sugarcane mosaic virus, is one of the main diseases in sugarcane production areas in Brazil. Thus, the identification of new sources of resistance for use in future introgression crosses is key for reliable economic gains. Here, we aimed to screen a diversity panel of 98 sugarcane genotypes for SMD under natural infection conditions, to investigate virus-specific amplicons from SCMV coat protein gene (CP), and identify marker-trait associations via association mapping using Amplified Fragment Length Polymorphism (AFLP) and Simple Sequence Repeats (SSR). The highest SMD incidence (26.53%) was observed eight months after planting, with significant differences (p<0.01) among genotypes and a means-based broad-sense heritability of 62.49% with a noticeable contribution of Saccharum spontaneum to SMD resistance. The CP sequence analysis revealed no variation among the four selected plant samples, which phylogenetic analysis revealed clustering with the RIB-1 strain while putative amino acid substitutions indicate a new SCMV isolate. From a subset of 135 SSR and 663 AFLP markers, selected after quality control, 91 markers were associated with response to SCMV (p <0.05) by simple linear regression, and 24 were significant at p <0.01. Four out these 24 fit in a stepwise regression at p <0.05, all contributing for the resistance to SMD, and are present in thirteen genotypes showing no SMD symptoms. These four markers collectively explain 29.95% of trait variation, while individually explain from 5.51 to 14.02%, and may correspond to new genomic regions conferring genetic resistance to SMD which investigation is worthwhile.
Keywords: AFLP; Association mapping; Sources of resistance; SSR; Sugarcane mosaic disease